Enhanced photocatalytic performance of protonated graphite carbon nitride/molybdenum sulphide heterojunction for degradation of methyl orange dye. (10th November 2021) - Pan, Yusong; Yin, Minyuan; Fang, Hongjun; Xu, Linfeng; Yan, Hanxian; Pan, Chengling
ABSTRACT: Protonated g-C3 N4 /MoS2  heterojunction with enhanced photocatalytic activity was prepared by treating g-C3 N4 /MoS2 with formic acid and using a hydrothermal method. The microstructure and morphology of the heterojunctions were analysed by XRD, FTIR, SEM, TEM, and XPS technology, respectively. The photodegradation experiment results verified that the formic acid treatment has a positive effect on the photocatalytic performance of g-C3 N4 /MoS2 heterojunctions. The as-prepared protonated g-C3 N4 /MoS2 composite with 5 wt% of MoS2 exhibited the highest photodegradation rate and photodegradation kinetic constant ( k ) for degradation of methyl orange (MO) dye. The activated species trapping experiment revealed that the superoxide radical (·O2 − ) plays an important role for degradation of MO dye. Furthermore, the investigation on the photocatalytic mechanism inferred that the enhanced photocatalytic property of protonated g-C3 N4 /MoS2 composite could be attributed to the Z-scheme electron migration mechanism in composite and the improved photo-induced electron-hole separation.